CARCINOGENICITY STUDY OF MONOSODIUM ASPARTATE IN FISCHER 344 RATS: 100 WEEKS TREATMENT - Nakamura, Yoshiyuki; Tao, Ming; Matsuda, Hirofumi; Kitahori, Yoshiteru; Naito, Hiroaki; Kitamura, Motokazu; Hiasa, Yoshio; Matsui, Emi; Konishi, Noboru (Journal of Toxicologic Pathology, 1996)
The carcinogenicity of monosodium aspartate (MSA), an amino acid, was examined in Fischer 344 rats of both sexes. MSA was added to the drinking water of groups of 50 male and 50 female rats at levels of 2.5% or 5.0% for 100 wk. There was a dose-dependent reduction in the mean final body weights of rats treated with MSA. Body and organ weights, urinalysis, and hematological evaluations revealed no evidence of adverse effects associated with the test chemical. However, hyperplasias of the renal papillae and hyperplasias of the urinary bladder were observed in MSA-treated groups, but not in the controls. In the kidneys, hyperplasias were found in 24% (10/41) and 7% (4/44) in males fed 5% MSA and 2.5% MSA, and 22% (9/36) and 3% (1/40) in females, respectively. Hyperplasias of the urinary bladder occurred in 5 of the male rats and 3 of female rats receiving the 5%-dose. No calcification or necrosis of the renal papillae was observed. While many other tumors developed in all groups, including the controls, the organ distribution of these neoplasms and their histological characteristics did not differ significantly from those known to occur spontaneously in this strain. These results suggest that development of hyperplasias of the urinary tract may occur due to a direct-action of MSA.